2020
DOI: 10.21203/rs.3.rs-20670/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the contribution of tropical cyclone seeds to changes in tropical cyclone frequency due to global warming in high-resolution multi-model ensemble simulations

Abstract: Previous projections of the frequency of tropical cyclone genesis due to global warming, even in terms of sign of the change, depends on the chosen model simulation. Here, we systematically examine projected changes in tropical cyclones using six global atmospheric models with medium-to-high horizontal resolutions included in the sixth phase of the Coupled Model Intercomparison Project/High-Resolution Model Intercomparison Project. Changes in the frequency of tropical cyclone genesis could be broken down into … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…By taking into account seed variability, we demonstrate that the new framework reproduces the hurricane annual cycle much more consistently than the probability alone, and in particular, is able to capture the sharp hurricane season. It also provides a unified framework to view TC annual cycles from various basins, sources (both observations and model simulations), and numerical experiments.Previous studies have shown that the probability and seed framework could help explain diverging responses of TC frequency to radiative climate forcing induced by greenhouse gases(3,11,21,22). Here we test and validate that the new framework also works in a different scenario: climatological variations driven by the annual cycle radiative forcing.…”
mentioning
confidence: 71%
“…By taking into account seed variability, we demonstrate that the new framework reproduces the hurricane annual cycle much more consistently than the probability alone, and in particular, is able to capture the sharp hurricane season. It also provides a unified framework to view TC annual cycles from various basins, sources (both observations and model simulations), and numerical experiments.Previous studies have shown that the probability and seed framework could help explain diverging responses of TC frequency to radiative climate forcing induced by greenhouse gases(3,11,21,22). Here we test and validate that the new framework also works in a different scenario: climatological variations driven by the annual cycle radiative forcing.…”
mentioning
confidence: 71%
“…Yoshida and Fudeyasu (2020) found that the frequency of the easterly wave flow pattern, which often transforms into tropical depressions, is the highest in October. Considering the small number of tropical disturbances that transform into TCs, we need to understand how the activity of seeds of TC and their survival rate (the fraction of TC formation to tropical disturbances; Lee et al., 2020; Sugi et al., 2020; Yamada et al., 2021) are modulated by the BSISO and improve the model performance of TC genesis predictions based on this understanding.…”
Section: Summary and Discussionmentioning
confidence: 99%